STUDI HEMATOLOGI IKAN NILA (Oreochromis niloticus) DI DANAU TOGA DESA BETENGON KECAMATAN DONDO KABUPATEN TOLITOLI - Aliyas Aliyas; Darmawati Darmawati; Dewi; Fitriani Basrin (Universitas Mataram, 2024)
Hematological examination can be used as a way to help diagnose diseases in fish effectively and quickly. Therefore, a study of the blood picture, in this case the profile of several hematological parameters in tilapia (Oreochromis niloticus), needs to be done by observing the picture of red blood cells (erythrocytes), and white blood cells (leukocytes). Fish blood sampling was carried out at Lake Toga, Betengon Village, Dondo District, Tolitoli Regency. Analysis of total erythrocyte and total leukocyte analysis was carried out at UPT Puskesmas Managaisaki Tolitoli. The results obtained in this study are observations of blood images including red blood cells (erythrocytes) and white blood cells (leukocytes) in Lake Toga, Betengon Village. As for the results of observations on the blood picture of tilapia (Oreochromis niloticus) it is known that the average total erythrocytes and leukocytes in Lake Toga, Betengon Village shows a normal range with a total of 2,170,000 cells/mm3 for red blood cells and 35,850 cells/mm3 for white blood cells. Based on these results, it can be concluded that the tilapia in Lake Toga, Betengon Village, shows a picture of healthy blood. Keywords: Oreochromis niloticus, erythrocytes, leukocytes